Shaping the Skyline: The World According to Real Estate Visionary Julien Studley - Hellman Peter (American : John Wiley, 2004)
Julien Studley is one of the great leaders in the real estate industry. He built a thriving business based upon hard work, creativity, integrity, and skill. In a time when the news is full of corporate scandal and executive excess, it is gratifying to read Julien Studley’s story–he has always focused on doing the right thing. As Julien’s career and life amply attest, how you conduct business is integral to your success. Julien’s talent is unique and his story inspirational."
—Jerry I. Speyer
President and CEO
Tishman Speyer Properties
"An intimate portrait of Julien Studley, a man whose keen intellect, ambition, and courage have made him into one of the most successful business leaders of our time–a true real estate visionary."
—Rep. Richard Gephardt (D-MO)
Julien Studley’s story is much more than a standard corporate biography. It is, in fact, a riveting tale of late twentieth century corporate America, a time in which America’s global business dominance was built on the vision and sacrifice of individualists who were strong, stubborn, and above all, resourceful. Shaping the Skyline examines Studley’s long and distinguished career and reveals his unique approach to real estate, negotiating strategies, leadership, and management that have led him to create one of the most successful commercial real estate companies in the nation.
Keywords: Studley Inc - History; Studley, Julien; Real estate agents; New York; Biography